2018
DOI: 10.1111/hsc.12617
|View full text |Cite
|
Sign up to set email alerts
|

Empowering elderly Iranians through a social group work intervention: A trial study to assess the effect of the intervention on participants' quality of life

Abstract: We designed and ran an empowerment-oriented social group work intervention to assess whether the intervention could improve the quality of life of older Iranians. The intervention consisted of nine group sessions that focused on capacity building and increasing individual competences, environmental resources and opportunities. Using a randomised controlled trial (RCT), 60 elderly people (30 men and 30 women in the intervention and control groups) from Social Services Centres in Tehran Municipality participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The result of this study mainly showed the influence of BKL activities on the psychological well-being of the elderly and their family caregiver. The similar result was found by Salomoni et al (2018) with an improvement of psychological QoL among females (9.41 %) and male (9.75%) Iranian elderly after conducting public health intervention, which included capacity building sessions on selfconfidence and self-esteem topics. In addition, the caregiver psychological well-being was associated with the coping mechanism, emotional distress, perceived burden and health status of the caregiver (Rodriguez-Perez et al, 2017).…”
Section: Methodssupporting
confidence: 80%
“…The result of this study mainly showed the influence of BKL activities on the psychological well-being of the elderly and their family caregiver. The similar result was found by Salomoni et al (2018) with an improvement of psychological QoL among females (9.41 %) and male (9.75%) Iranian elderly after conducting public health intervention, which included capacity building sessions on selfconfidence and self-esteem topics. In addition, the caregiver psychological well-being was associated with the coping mechanism, emotional distress, perceived burden and health status of the caregiver (Rodriguez-Perez et al, 2017).…”
Section: Methodssupporting
confidence: 80%
“…One of the most significant prolonged challenges will be the socioeconomic effects of old age. In Iran, some local activities are entrusted to older adults while involving them in the boards of directors, which will lead to their activity and participation in society and, as a result, the promotion of active aging (60).…”
Section: Discussionmentioning
confidence: 99%
“…This condition happened because of gratitude and their position as elderly widows. Elderly female heads of household tend to be stigmatized due to age discrimination, changes in family roles due to widowhood, and exclusion from society 8 . However, this did not occur in this study due to cultural differences.…”
Section: Daily Activities and Economic Fulfillmentmentioning
confidence: 99%
“…These older women's social, physical, and economic limitations are significant obstacles to accessing food to meet their daily needs. Aging elderly often experience social exclusion due to age discrimination and changes in roles in the family and society 8 . Aging is often considered outside the social order or loss of independence from an individual, resulting in access to resources, carrying out social interactions, and getting public services to be hampered for every aging individual.…”
Section: Introductionmentioning
confidence: 99%